The role of resting-state perfusion CMR in the evaluation of microvascular obstruction in patients with acute myocardial infarction: A clinical perspective - Yingying Hu; Zidi Wang; Zheng Sun; Zhi Liu; Jie Lu (European Journal of Radiology Open)
Objectives: To investigate the clinical application value of cardiac resting-state perfusion weight imaging (rs-PWI)-derived parameters in patients with acute myocardial infarction (AMI) complicated by microvascular obstruction (MVO). Methods: Overall, 300 patients with AMI were prospectively enrolled, and divided into the MVO and non-MVO groups, based on the presence of MVO in the infarcted myocardium. Differences in rs-PWI imaging parameters, and the diagnostic value of rs-PWI in reperfusion myocardial ischemia at segment level and MVO were quantitatively evaluated. Results: The average age was 58.60 ± 13.03 years, and 246/300 (82 %) were males. The MVO group had 176 patients (mean age: 57.90 ± 12.47), including 140 (80 %) males. The left ventricular (LV) volumes occupied by the infarcted myocardium were 19.60 ± 2.70 %LV and 15.20 ± 3.40 %LV in the MVO and non-MVO groups, respectively (P < 0.05). There were 679 LGE positive segments in the MVO group (679/2816, 24.1 %). The area under curve (AUC), sensitivity, specificity, and Jordan index of rs-PWI for MVO diagnosis were 0.95(0.89–0.99), 94.3 %, 93.4 %, and 0.88, respectively. At the segmental level, the maximum rising slope was higher in the MVO than non-MVO group (15.09 ± 2.64 vs. 6.21 ± 1.25, P < 0.05). The time to peak 20 %-80 % was shorter in the MVO group (4.07 ± 0.79 vs. 7.75 ± 1.03, P < 0.05). Comparison revealed differences in perfusion indices (MVO: 0.32 ± 0.09 vs. non-MVO: 0.42 ± 0.04, P < 0.05). The highest diagnostic value for MVO among rs-PWI parameters was AUC 0.90(0.84–0.97), sensitivity 94.1 %, specificity 88.7 %, and accuracy 91.1 %. Conclusion: CMR rs-PWI sequence effectively evaluates reperfusion myocardial ischemia complicated with MVO, while the perfusion index has high diagnostic value in quantifying myocardial blood flow potential.